Thermochronology of the Maures-Tanneron crystalline basement: insights for SW Europe Triassic to Miocene tectonic history - Louise Boschetti; Y. Rolland; F. Mouthereau; S. Schwartz; G. Milesi; P. Munch; M. Bernet; M. Balvay; D. Thiéblemont; M. Bonno; C. Martin; P. Monié (Swiss Journal of Geosciences)
Abstract This paper presents a thermochronological study of the Western European basement in the Maures-Tanneron massif (MTM), using zircon and apatite fission-track data, in addition to apatite (U-Th-Sm)/He analyses. The combination of these methods with inverse thermal modelling allows us to trace the thermal history of this massif from the Late Triassic to the present day. The study identifies several thermal events that are linked to two major tectonic phases at 120–40 Ma and 40–15 Ma. These new results prompt us to re-evaluate the thermal evolution and exhumation of Western European basement of the Provence region. We distinguish four episodes. (i) A period characterized by constant temperature contemporaneous with Triassic magmatic activity and Tethys rifting (ii) a period of sedimentary burial heating of the MTM associated with the Cretaceous Pyrenean rift evolution (iii) subsequent N–S Pyrenean inversion at 75 Ma, causing cooling and exhumation of the MTM, (iv) opening of the West European rift system and the Liguro-Provençal basin, which resulted in heating from 35 to 15 Ma and post 15 Ma cooling of the MTM. This study also provides insights into the paleogeography of the MTM and demonstrates its evolution at the cross-roads between the Pyrenean and Alpine orogens.